Vehicle Emission Factors of Solid Nanoparticles in the Laboratory and on the Road Using Portable Emission Measurement Systems (PEMS) - Giechaskiel, Barouch; Riccobono, Francesco; Vlachos, Theodoros; Mendoza-Villafuerte, Pablo; Suarez-Bertoa, Ricardo; Fontaras, Georgios; Bonnel, Pierre; Weiss, Martin (Frontiers in Environmental Science, 2015)
Emission inventories are used to quantify sources and identify trends in the emissions of air pollutants. They use vehicle-specific emission factors that are typically determined in the laboratory, through remote-sensing, vehicle chasing experiments and, more recently, on-board Portable Emission Measurement Systems (PEMS). Although PEMS is widely applied to measure gaseous pollutants, their application to Solid Particle Number (SPN) emissions is new. In this paper, we discuss the current status of determining SPN emission factors both on the chassis dynamometer and on-road using PEMS-SPN. First, we determine the influence of the measurement equipment, ambient temperature, driving style and cycle characteristics, and the extra mass of the PEMS equipment on the SPN emissions. Afterward, we present the SPN emissions under type-approval conditions as well as on the road of two heavy-duty diesel vehicles equipped with Diesel Particulate Filter (DPF) (one Euro VI), two light-duty diesel vehicles equipped with DPF, one light-duty vehicle equipped with a Port Fuel Injection engine (PFI), and seven Gasoline Direct Injection (GDI) passenger cars (two Euro 6). We find that cold-start and strong accelerations tend to substantially increase SPN emissions. The two heavy-duty vehicles showed emissions around 2×10^13 p/km (Euro V truck) and 6×10^10 p/km (Euro VI truck), respectively. One of the DPF-equipped light-duty vehicles showed emissions of 8×10^11 p/km, while the other one had one order of magnitude lower emissions. The PFI car had SPN emissions slightly higher than 1×10^12 p/km. The emissions of GDI cars spanned approximately from 8×10^11 p/km to 8×10^12 p/km. For the cars without DPF, the SPN emissions remained within a factor of two of the laboratory results. This factor was on average around 0.8 for the Euro 6 and 1.6 for the Euro 5 GDIs. The DPF equipped vehicles showed a difference of almost one order of magnitude between laboratory and on-road tests due to the different DPF fill state and passive regeneration during the tests. The findings of this study can (i) help improving the on SPN emissions and (ii) assist policy makers in designing effective test procedures for measuring SPN emissions of vehicles under real-world driving conditions.